Two new species of Stilbohypoxylon and the taxonomic positions of Hypoxylon cyclopicum, H. chionostomum and Anthostoma chionostoma - Hladki, Adriana Ines (2003)
Two new species of Xylariaceae, Stilbohypoxylon macrosporum and Stilbohypoxylon minor, are described, illustrated and compared with the other three species of the genus. A key to these taxa is provided. Hypoxylon cyclopicum is considered a later synonym of Kretzschmaria micropus. Hypoxylon chionostomum and Anthostoma chionostoma, which have been treated as synonyms by some authors, are in fact not closely related. Hypoxylon chionostomum is a good Hypoxylon species, whereas A. chionostoma is a later synonym of Leptomassaria simplex.